2013
DOI: 10.5194/acp-13-8551-2013
|View full text |Cite
|
Sign up to set email alerts
|

Sources and photochemistry of volatile organic compounds in the remote atmosphere of western China: results from the Mt. Waliguan Observatory

Abstract: The chemistry of the natural atmosphere and the influence by long-range transport of air pollution are key issues in the atmospheric sciences. Here we present two intensive field measurements of volatile organic compounds (VOCs) in late spring and summer of 2003 at Mt. Waliguan (WLG, 36.28° N, 100.90° E, 3816 m a.s.l.), a baseline station in the northeast part of the Qinghai-Tibetan Plateau. Most VOC species exhibited higher concentrations in late spring than in summer. A typical diurnal variation was observed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
72
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 58 publications
5
72
1
1
Order By: Relevance
“…Because of the relatively long atmospheric lifetime of ethane (Table 1), it contributed most of the measured alkane concentration in both years. This result is similar to those obtained at other mountain stations, irrespective of locations and seasons (Greenberg et al, 1996;Schmitt and Volz-Thomas, 1997;Sharma et al, 2000;Swanson et al, 2003;Helmig et al, 2008;Suthawaree et al, 2010;Xue et al, 2013). Alkyne, as represented solely by ethyne, had the lowest contribution among all VOC types, accounting for 5.3%-6.1% of total VOCs.…”
Section: Overview Of the Observed Vocssupporting
confidence: 75%
See 3 more Smart Citations
“…Because of the relatively long atmospheric lifetime of ethane (Table 1), it contributed most of the measured alkane concentration in both years. This result is similar to those obtained at other mountain stations, irrespective of locations and seasons (Greenberg et al, 1996;Schmitt and Volz-Thomas, 1997;Sharma et al, 2000;Swanson et al, 2003;Helmig et al, 2008;Suthawaree et al, 2010;Xue et al, 2013). Alkyne, as represented solely by ethyne, had the lowest contribution among all VOC types, accounting for 5.3%-6.1% of total VOCs.…”
Section: Overview Of the Observed Vocssupporting
confidence: 75%
“…However, Khwaja and Narang (2008) also reported a low ratio of 0.36 during nighttime for free tropospheric subsidence at Whiteface Mountain in the northeastern United States. Xue et al (2013) observed an even lower ratio of 0.25 at Mt. Waliguan in summer.…”
Section: Isomeric Pairs Of Pentanesmentioning
confidence: 92%
See 2 more Smart Citations
“…Monitoring of benzene levels at more background sites would, therefore, not only reveal background exposure levels, but also reflect the impact of regional social-economic changes. Unfortunately, monitoring at background or remote locations is scarce and sporadic in China (Guo et al, 2004;Tang et al, 2009;Suthawaree et al, 2010;Xue et al, 2013;Zhang et al, 2014). To fully understand the exposure levels and the potential health risks, long-term measurements are needed.…”
mentioning
confidence: 99%